The Four “X’s” SME Marketing Model: A Non-Technical Approach to Marketing for SMEs in Malaysia - Kee, Cheng Guan (2008)
Small and Medium Enterprises (SMEs) are extremely vital to the global economy as it contributes substantially to the gross domestic product and employment of a particular country. In Malaysia, there are more than half a million SMEs representing 99% of the total business establishment in the country. Malaysian SMEs contributes close to 32% of the gross domestic product and 56% of the total employment. Though important, SMEs in Malaysia still lack the competitiveness displayed in other SMEs around the region like Japan, Korea and China. There are many reasons for these prevalent weaknesses and one of them is the inability to adopt marketing as a business tool due to the lack of necessary marketing knowledge. Marketing is an essential business tool for all businesses to compete effectively in an extreme intense global business environment. Such argument has also been applied to small businesses throughout the world. Unfortunately, it has also been established that getting small business to adopt and implement marketing initiatives successfully is particularly challenging. From the literature aspect, there have been very limited studies done on small business marketing including SME Marketing in Malaysia. This dissertation hopes to provide a better insight into the key issues hindering SMEs in Malaysia from adopting marketing into their day to day business. It will also attempt to propose a simple, yet systematic SME Marketing model to help Malaysian SMEs compete effectively. The dissertation presents a qualitative analysis of data collected from a broad range of SMEs within the Malaysian SME industry. The data were obtained through a series of semi structured in-depth interviews with SME owner-managers, focusing particularly on their views about the importance, perception and understanding of marketing as well as the marketing standards within the sectors in which they compete. Findings reveal that SMEs in Malaysia do acknowledge the importance of marketing however it also reveals that most SMEs in Malaysia have a weak understanding of marketing which leads to the inability to take advantage of this essential tool. The implications are discussed and conclusions were drawn.